In silico identification of papaya genome-encoded microRNAs to target begomovirus genes in papaya leaf curl disease - Srivastava, Aarshi; Pandey, Vineeta; Singh, Nupur; Marwal, Avinash; Shahid, Muhammad Shafiq; Gaur, R. K. (Frontiers in Microbiology, 2024)
Papaya leaf curl disease (PaLCuD) is widespread and classified in the genus begomovirus (Geminiviridae), disseminated by the vector whitefly Bemisia tabaci. RNA interference (RNAi)-based antiviral innate immunity stands as a pivotal defense mechanism and biological process in limiting viral genomes to manage plant diseases. This study identified forty-eight predicted papaya-locus-derived candidates from twenty-three miRNA families, which were further investigated for targeting begomovirus genes. Premised all the four algorithms combined, capa-miR5021 was the most anticipated miRNA followed by capa-miR482, capa-miR5658, capa-miR530b, capa-miR3441.2 and capa-miR414 'effective' papaya locus-derived candidate capa-miRNA, and respected putative binding sites for targets at the consensus nucleotide position. It was predicted to bind and target mostly to AC1 gene of the complementary strand and the AV1 gene of the virion strand of different begomovirus isolates, which were associated with replication-associated protein and encapsidation respectively, during PaLCuD. These miRNAs were also found targeting betaC1 gene of betasatellite which were associated with retardation in leaf growth and developmental abnormalities with severe symptoms during begomovirus infection. In order to validate target prediction accuracy, we created an integrated Circos plot for comprehensive visualization of host-virus interaction. In silico-predicted papaya genome-wide miRNA-mediated begomovirus target gene regulatory network corroborated interactions that permit in vivo analysis, which could provide biological material and valuable evidence, leading to the development of begomovirus-resistant papaya plants. The integrative nature of our research positions it at the forefront of efforts to ensure the sustainable cultivation of papaya, particularly in the face of evolving pathogenic threats. As we move forward, the knowledge gained from this study provides a solid foundation for continued exploration and innovation in the field of papaya virology and to best of our knowledge, this study represents a groundbreaking endeavor, undertaken for the first time in the context of PaLCuD research.